Insulin-like growth factor-binding protein-3 is induced by tamoxifen and fulvestrant and modulates fulvestrant response in breast cancer cells - Flynn, Keenan L.; Zheng, Yan; Sowers, Janel Y.; Masangya, Nefretiri J. T.; Houston, Kevin D. (Frontiers in Oncology, 2024)
IntroductionInsulin-like growth factor binding protein-3 (IGFBP-3) exerts varying effects on estrogen receptor alpha (ERα)-positive and triple-negative breast cancer (TNBC) cells. In ERα-positive cells, IGFBP-3 is antiproliferative and proapoptotic. In contrast, IGFBP-3 stimulates proliferation in triple-negative breast cancer (TNBC) cells via EGFR activation.MethodsTo identify potential mechanisms that underlie the opposing effects of IGFBP-3 on these two breast cancer subtypes, IGFBP-3 expression was determined in cell line models of both ERα-positive breast cancer and TNBC, and cells were treated with antiestrogens tamoxifen and fulvestrant. Results and discussionMCF-7 and T-47D cells expressed low levels of IGFBP-3 when compared to MDA-MB-231 and MDA-MB-468 cells. MCF-7 cells with acquired resistance to the selective estrogen receptor degrader fulvestrant expressed high IGFBP-3 and MCF-7 cells with constitutive IGFBP-3 expression were fulvestrant resistant. IGFBP-3 expression was increased in all cell lines upon treatment with fulvestrant or the selective estrogen receptor modulator tamoxifen and both fulvestrant and tamoxifen increased TNBC cell proliferation. Further, IGFBP-3 expression was increased by treatment with the GPER1 agonist G-1 and attenuated upon treatment with P17, a YAP/TAZ inhibitor. These data suggest that IGFBP-3 modulates breast cancer cells and is a mediator of breast cancer cell response to fulvestrant and tamoxifen.